Simulation of the Effect of Flow Ratio on Methyl Caproate Composition in Fractionated Methyl Ester Based on Palm Kernel Oil - William Tandra; Budi Husodo Bisowarno; Tedi Hudaya (International Journal Labs, 2025)
This research consists of five steps, first is literature review and Aspen Plus simulator review, this review step will not only provide initial data and assumptions, but also provide which thermodynamics data suitable to be used in Aspen Plus for this research. Second step is the data collection step, the data collected from actual recorded data such as temperature, pressure, and flow rate from one of oleochemicals plants in the June 2023 period complete with the analysis results. The data and analysis results are collected from several days in the month and selected based on normal running conditions of the plant without any interruptions. Third is the process modeling with Aspen Plus simulator using the data collected from literature review and actual plant data. Fourth step is validation of the process model using actual plant data with different modes. The last step is simulation of the process using the valid model to predict the product composition based on predetermined process parameter variation. Based on the actual plant data, valid model obtained using RadFrac Unit Operation, with reflux ratio 150, stage count at 32 stages, and feed stage at stage 23. Process parameter variation used in the simulation are reflux ratio and side product flow ratio with +/- 10% range. Based on the simulation result, reflux ratio affects methyl caproate product composition more than side product flow ratio in first methyl ester fractionation column. This model has the potential to be implemented in the plant to predict the methyl caproate composition in case of feed composition changes or deviation on the product composition itself.